Deteksi Notifikasi Suspend pada Aplikasi Ojek Online Menggunakan Metode MOORA - Wijiono, Aditya Kusuma; Vitianingsih, Anik Vega; Kacung, Slamet; Maukar, Anastasia Lidya; Pamudi, Pamudi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Online motorcycle taxi drivers often face the risk of account suspension due to violations of rules that are not always clear or understood by them. This ignorance can cause drivers to be unaware of actions that can lead to suspension, which can impact their income and reputation. To overcome this problem, this study proposes the use of the Multi-Objective Optimization based on Ratio Analysis (MOORA) method in detecting and providing early notification regarding potential suspension. The MOORA method is used to analyze various parameters related to violations, such as the frequency and type of violations, as well as the number of accumulated violation points. By processing this data, the developed system can predict the possibility of suspension and provide notification to the driver. The results of the application of the MOORA method show that this system is effective in providing accurate notifications and can help drivers avoid actions that have the potential to cause suspension. The application of this system has the potential to reduce the number of suspension cases and increase driver awareness of actions that must be avoided.